Failure Mechanism Analysis of the Stochastic Galerkin Method in EMC Simulation Considering Geometric Randomness - Bai, Jinjun; Hu, Bing; Wan, Yixuan (Applied Computational Electromagnetics Society Journal (ACES), 2023)
By virtue of its high calculational accuracy and efficiency, the stochastic Galerkin method (SGM) has been successfully applied many times in electromagnetic compatibility (EMC) simulation in recent years. This paper proposes a calculating example taking geometric uncertainty factors into consideration. As is proved in the paper, there is a relatively large error when using the SGM to solve the example mentioned above. According to failure mechanism, the fundamental reason of the failure of the simulation lies in the additional error caused by using numerical integration to solve the inner product formula. Meanwhile, it is proved that no additional errors are introduced when using the stochastic collocation method (SCM), so the SCM is better than the SGM in stability. In the end, the paper revised the general selective strategy for uncertainty analysis methods, thus providing theoretical basis for their universal application in EMC field.